Horizontal effect of the rules on international jurisdiction in Regulation nº 1215/2012 (notes on a withdrawn request for a preliminary ruling) - Requejo Isidro, Marta (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
In December 2019, the Court of Appeal of England and Wales requested the Court of Justice to decide whether Article 4 (1) of Regulation 1215/2012, confers a directly enforceable right upon a person domiciled in a Member State. For the case of a positive answer, it asked as well about remedies. The request was withdrawn later. This paper addresses what in all likelihood, according to the author, would have been the answer of the Court of Justice. It also submits that, under specific circumstances, a different reading of certain provisions of the Regulation might be possible, as well as suitable to reinforce the protection of persons domiciled in the European Union and to ensure the enforcement of essential legislative policies.
Keywords: international jurisdiction; individual rights; remedies; anti-suit injunctions; protection of the weaker party; safeguard of essential policies; EU Member States; third States